Student’s evaluation of university teaching. What should we know? (Boletin Médico de Postgrado, 2024)
Student’s evaluation is a constant concern of teachers at all educational levels. Evaluation allows teaching and learning to be connected, providing information that allows value judgments to be made regarding student learning allowing decisions to be made to adjust the educational process. The purpose of this essay is to create a brief but substantial expository text on the most important theoretical foundations of the evaluation of learning aimed at university teachers with non-teaching professional training. The review, interpretation and analysis of the works of different authors was carried out to summarize the most common findings regarding the conceptualization of evaluation, evolution, elements, steps, functions and types. Finally, new concepts in learning evaluation and their perception in relation to their functionality as a learning tool are described. It is concluded that the conceptualization that teachers have about evaluation determines the way in which they evaluate students; Therefore, knowing the conceptual theoretical elements allows the university professor to adopt a coherent position in this regard, planned according to the needs and realities of the educational process in which they are immersed together with their students. Furthermore, it contributes to improving the teacher's work, as it motivates self-analysis and reflection of their evaluation practice, and favors the development of their skills as effective evaluators.